The Trend of Engaging Role-Playing Communities on Telegram for Learning Written English - Aulia Aldilah Bahar; Moh Iqbal Firdaus; Yudhie Indra Gunawan (Institut Agama Islam Negeri Palopo, 2025)
The purpose of this study is to determine the effect of the role-playing community in English writing skills for its members. The research used in this study is in the form of qualitative methods with a descriptive approach. The instruments used are structured interviews and passive observation. Interviews were conducted with ten respondents and observations were made by five respondents who actively wrote in a private channel on Telegram. The results showed that the role-playing community had a positive impact on developing the English writing of its members, and fostered an increase in members' confidence in writing English. The challenges experienced by respondents are the lack of vocabulary and concerns about grammatical errors, but participants usually overcome them by using Grammarly or translator applications. Observations of five active members writing on their personal channels showed progress over time, for example in the cohesiveness, clarity, and grammatical accuracy of their writing over time. These findings show that role-playing communities can help people to develop their English writing because they have a good impact.